Production and Characterization of Alumina and Steatite Based Ceramic Insulators - Sonmez, Mehmet Seref; Kaplan, Sevki Samet; Altun, Caglar; Acma, Mahmut Ercan (Informa UK Limited, 2019)
In this study, production of alumina and steatite containing ceramic insulators as thermostat material was realized by investigating the composition, pressing pressure and sintering temperature. 90...